2004
DOI: 10.1148/radiol.2321030174
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Arthritis–related Lung Diseases: CT Findings

Abstract: Rheumatoid arthritis is associated with four CT patterns: usual interstitial pneumonia, nonspecific interstitial pneumonia, bronchiolitis, and organizing pneumonia. The most common CT features of rheumatoid arthritis-related lung disease were GGO and reticulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
192
2
16

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(215 citation statements)
references
References 43 publications
(51 reference statements)
5
192
2
16
Order By: Relevance
“…27 There are data demonstrating excellent correlation between the histopathologic pattern found on surgical lung biopsy and the radiographic pattern found on HRCT scans in patients with IPF. 8,28 The correlation between histopathologic and radiographic patterns in RA-ILD patients has not been as rigorously studied, but it appears that the same correlation is present (Table 1).…”
Section: Ra-ild: Radiographic-histopathologic Correlationmentioning
confidence: 93%
See 1 more Smart Citation
“…27 There are data demonstrating excellent correlation between the histopathologic pattern found on surgical lung biopsy and the radiographic pattern found on HRCT scans in patients with IPF. 8,28 The correlation between histopathologic and radiographic patterns in RA-ILD patients has not been as rigorously studied, but it appears that the same correlation is present (Table 1).…”
Section: Ra-ild: Radiographic-histopathologic Correlationmentioning
confidence: 93%
“…Lung biopsy specimens were available in 14 of these 19 patients, and all patients showed UIP pattern. Tanaka et al 27 demonstrated that 41% of a retrospective RA-ILD cohort had UIP pattern seen on HRCT scans, with 30% showing a fibrotic NSIP pattern. Of the 26 patients with UIP pattern seen on HRCT scan, only 4 patients underwent lung biopsies; 2 patients had UIP, and 2 patients had fibrotic NSIP.…”
Section: Ra-ild: Radiographic-histopathologic Correlationmentioning
confidence: 99%
“…As abnormal radiological patterns seen on high-resolution computed tomography (HRCT) scans accurately reflect the underlying histological patterns revealed through lung biopsy [9–11], we recently performed HRCT scans on 126 patients with early or longstanding RA [12]. By evaluating one or two predominant abnormalities in each patient’s HRCT findings and observing the distribution and extent of all abnormalities in the lungs, we gave each patient an HRCT-based diagnosis, such as an interstitial pneumonia (IP) pattern or a bronchiolitis pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent intensive studies in collaboration with pathologists and radiologists have endorsed its differentiation from other types of IP, gaining the term NSIP, a broad acceptance [39,40]. NSIP pattern of lung injury, itself further subdivided into cellular and fibrotic NSIP, is the most common pattern of IP in all CTDs except for RA, in which UIP pattern pathology may be more common [41,42]. NSIP lung injury is characterized by diffuse, although often variable, alveolar septal thickening due to collagen deposition.…”
Section: Nonspecific Interstitial Pneumonia (Nsip)mentioning
confidence: 99%